Interaction Of Sumatran Orangutan (Pongo abelii) And Human In Semi-Wild Condition At Bukit Lawang, Gunung Leuser National Park, Sumatera - Nazaruddin, Fatin Nabila Md (2018)
This study aimed to investigate the Sumatran orangutans’ behavioural responses and Sumatran orangutans’ space use toward number of tourists and rangers at forest and feeding site in Bukit Lawang, Gunung Leuser National Park, Sumatera, Indonesia. This research also seeks to investigate tourists’ perception, satisfaction and awareness of Sumatran orangutans’ welfare at Bukfeeding feeding site. The behavioural study was done from September 2014 until March 2015 and the data of spatial uses of orangutans were collected from September 2013 until March 2015.